Apparent Competition in Two-Sided Platforms - Gokhan Guven; Eren Inci; Antonio Russo (Center for Economic Studies and ifo Institute (CESifo), 2017)
We study a platform's design of membership and transaction fees when sellers compete and buyers cannot observe the prices and features of goods without incurring search costs. The platform alleviates sellers' competition by charging them transaction fees that increase with sales revenue, and extracts surplus via membership fees. It prices consumers' membership below its cost to encourage their search. Examples include malls and online marketplaces. Most malls do not charge for parking while most lease contracts include percentage rents as well as fixed rents. Online marketplaces charge sellers for membership and per transaction while letting consumers access website for free.
Keywords: D21; D40; D83; L13; R33; 330; consumer search; membership fees; retail agglomeration; transaction fees; two-sided platforms